Non-coding RNA-Associated ceRNA Networks in a New Contrast-Induced Acute Kidney Injury Rat Model - Wei Cheng; Xu-Wei Li; Ye-Qing Xiao; Shao-Bin Duan (Elsevier, 2019)
Contrast-induced acute kidney injury (CI-AKI) is a severe complication of intravascular applied radial contrast media, and recent progress in interventional therapy and angiography has revived interest in explaining detailed mechanisms and developing effective treatment. Recent studies have indicated a potential link between CI-AKI and microRNA (miRNA). However, the potential non-coding RNA-associated-competing endogenous RNA (ceRNA) pairs involved in CI-AKI still remain unclear. In this study, we systematically explored the circRNA or lncRNA-associated-ceRNA mechanism in a new rat model of CI-AKI through deep RNA sequencing. The results revealed that the expression of 38 circRNAs, 12 lncRNAs, 13 miRNAs and 127 mRNAs were significantly dysregulated. We performed Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathway analyses for mRNAs with significantly different expression and then constructed comprehensive circRNA or lncRNA-associated ceRNA networks in kidney of CI-AKI rats. Thereafter, two constructed ceRNA regulatory pathways in this CI-AKI rat model-novel_circ_0004153/rno-miR-144-3p/Gpnmb or Naglu and LNC_000343/rno-miR-1956-5p/KCP-were validated by real-time qPCR. This study is the first one to provide a systematic dissection of non-coding RNA-associated ceRNA profiling in kidney of CI-AKI rats. The selected non-coding RNA-associated ceRNA networks provide new insight for the underlying mechanism and may profoundly affect the diagnosis and therapy of CI-AKI. Keywords: non-coding RNA, ceRNA networks, CI-AKI, rat model